IMPLEMENTASI INOVASI KEBIJAKAN DALAM PENYELENGGARAAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) DI KABUPATEN DONGGALA - Fadila Putri Utami; Gustafianul Shiddiq Akbar; Hajria Hajria; Ni KMG Tri Purwati (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
To achieve high-quality government administration as outlined in Presidential Regulation No. 95 of 2018, which focuses on delivering optimal public services, ensuring transparency, accountability, efficiency, and fostering clean governance, local governments must develop innovative policies centered on Electronic-Based Government Systems (SPBE) . This research aims to examine the implementation of innovation policies in implementing SPBE in Donggala City. This research utilized both primary and secondary data collected through interviews, observations, and documentation. The data were analyzed to derive conclusions about the issues under study. The findings reveal that the innovation policies for implementing SPBE in Donggala City have been executed effectively, evident in the development of service applications that enhance public accessibility. Nevertheless, challenges persist, including limited public awareness about the applications and a shortage of human resources with specialized technical skills in Information and Communication Technology (ICT).